A morphological and molecular reinvestigation of Janickina pigmentifera (Grassi, 1881) Chatton 1953 – an amoebozoan parasite of arrow-worms (Chaetognatha). Issue 11 (30th November 2021) - Volkova, Ekaterina; Kudryavtsev, Alexander
Abstract : Amoebozoan parasites of arrow-worms (Chaetognatha) were isolated from their hosts living in plankton of the Bay of Villefranche (Mediterranean Sea). Based on the light microscopic characters, the amoebae were identified as Janickina pigmentifera (Grassi, 1881) by their limax locomotive form and due to the presence of the intracellular symbiont, Perkinsela amoebae, surrounded by a layer of pigment granules. Sequences of the 18S rRNA gene of both J. pigmentifera and its symbiont were obtained for the first time. The molecular phylogenetic analyses of 18S rRNA gene placed J. pigmentifera within the genus Neoparamoeba, a taxon also characterized by the presence of a symbiont, known as Perkinsela amoebae -like organism (PLO). The 18S rRNA gene sequence of P. amoebae from J. pigmentifera grouped with the sequences of 18S rRNA genes of PLOs from Neoparamoeba branchiphila and Neoparamoeba invadens . The first photo documentation of the light microscopic features of J. pigmentifera, such as locomotive form, the morphology of the nucleus and P. amoebae have been provided. The new results support the affinity of J. pigmentifera with the family Paramoebidae suggested previously based on the presence of PLO. In contrast to Janickina, typical members of Paramoebidae ( Neoparamoeba and Paramoeba ) have a flattened, dactylopodial locomotive form. This discrepancy in morphology can be explained by the obligate parasitic lifestyle of Janickina .